2022
DOI: 10.1200/jco.21.02767
|View full text |Cite|
|
Sign up to set email alerts
|

Somatic Genomic Testing in Patients With Metastatic or Advanced Cancer: ASCO Provisional Clinical Opinion

Abstract: PURPOSE An ASCO provisional clinical opinion offers timely clinical direction to ASCO's membership following publication or presentation of potentially practice-changing data from major studies. This provisional clinical opinion addresses the appropriate use of tumor genomic testing in patients with metastatic or advanced solid tumors. CLINICAL CONTEXT An increasing number of therapies are approved to treat cancers harboring specific genomic biomarkers. However, there is a lack of clarity as to when tumor geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 214 publications
(290 reference statements)
0
101
0
2
Order By: Relevance
“…Patient-Clinician Communication 49 (http://ascopubs.org/doi/10.1200/JCO.2017.75.2311)Integration of Palliative Care into Standard Oncology Care 53 (http://ascopubs.org/doi/10.1200/JCO.2016.70.1474)Biomarkers for Adjuvant Endocrine and Chemotherapy in Early-Stage Breast Cancer 50 (http://ascopubs.org/doi/10.1200/JCO.22.00069)Somatic Genomic Testing in Patients With Metastatic or Advanced Cancer 54 (https://ascopubs.org/doi/10.1200/JCO.21.02767)…”
Section: Additional Resourcesmentioning
confidence: 99%
“…Patient-Clinician Communication 49 (http://ascopubs.org/doi/10.1200/JCO.2017.75.2311)Integration of Palliative Care into Standard Oncology Care 53 (http://ascopubs.org/doi/10.1200/JCO.2016.70.1474)Biomarkers for Adjuvant Endocrine and Chemotherapy in Early-Stage Breast Cancer 50 (http://ascopubs.org/doi/10.1200/JCO.22.00069)Somatic Genomic Testing in Patients With Metastatic or Advanced Cancer 54 (https://ascopubs.org/doi/10.1200/JCO.21.02767)…”
Section: Additional Resourcesmentioning
confidence: 99%
“…Traditionally, BRCA testing has been conducted in germline DNA triggered by a familial aggregation of cancer. Recent studies have demonstrated that a significant proportion of mutation carriers are undiagnosed due to the lack of a significant family history of cancer [ 18 , 42 , 98 ], leading to changes in the recommendations for genetic testing. As an example, testing is now recommended for all metastatic prostate cancer patients, regardless of their personal or family history of cancer [ 99 ].…”
Section: The Challenge Of Testing: Searching For Hrd Scarmentioning
confidence: 99%
“…ESMO and NCCN guidelines [ 98 , 101 , 102 ] recommend pre-test counseling to determinate the most appropriate test for each patient and specific post-test counseling when results are available. Table 3 summarizes the current recommendations for testing based on international clinical guidelines.…”
Section: The Challenge Of Testing: Searching For Hrd Scarmentioning
confidence: 99%
“…Another relevant aspect to consider is the timing when to perform NGS in cancer patients. Although the presence of tumor-agnostic markers ( NTRK fusions, TMB and MSI) provides the premise for the use of sequencing in all tumors [ 59 ], ESMO guidelines recommend NGS just for patients with non-squamous NSCLC, ovarian carcinoma, prostate carcinoma and cholangiocarcinoma, so that, other than in these indications, the use of NGS should be considered on a case-by-case basis [ 60 ]. However, data from our analysis also highlight that about 20% of patients with a therapeutic suggestion from our MTB did not receive any systemic treatment following the MTB because of death or poor performance status not allowing further therapy.…”
Section: Discussionmentioning
confidence: 99%